PROSPECTION AND ESTIMATION OF UNCONVENTIONAL HYDROCARBON DEPOSITS IN UKRAINE - Mykhailov, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article discusses problems of geological and economic evaluation of unconventional hydrocarbon resources, mainly shale gas. Purpose of work is analysis of the existing methods of evaluation and calculation of hydrocarbons reserves; determination of the most important factors and criteria of their evaluation. Modern methods of prospecting, geological and economic estimation of unconventional hydrocarbon resources are analyzed. The main factors of localization and prognosis criteria of unconventional hydrocarbon deposits associated with shale strata and sealed reservoirs are the size of shale basin area, depth of production formation, the thickness of the shale horizons, the age of host rocks, features of occurrence, structural, lithological, mineralogical and geochemical features (thermal maturity of species), high content of soil organic matter and organic carbon, total porosity and permeability, increased rate of rocks fracturing. All there searches about the problems of unconventional hydrocarbons should be carried out in three stages: initial, detailed and estimated. The basic formula for evaluation of shale gas resources is given, with additional parameters of quantitative evaluation of unconventional gas resources in the compacted rocks being characterized. The coefficients of filling traps for productive horizons of Dnieper-Donets Basin are given. These data are proposed to use as additional coefficients for formula correction. Factors that are important at n the estimation of shale gas resources are examined. The most important factor for unconventional hydrocarbon types is the coefficient of fracturing, which largely affects the properties of collector rocks. The differentiation coefficient of perspective areas depending on complexity the geological structure is also proposed to be taken into account. Coefficients used for different regions of the world and the Dnieper-Donetsk region are shown. The coefficient of filling trap, the coefficient of fracturing, the differentiation coefficient of perspective areas depending on complexity the geological structure, the probability coefficients are the coefficients proposed to use as additional parameters for calculation unexplored resources of shale gas. Masic data about expected resources of shale gas in Eastern oil and gas region are shown.